2013
DOI: 10.1075/ijcl.18.4.01bar
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and usage-based grammar

Abstract: Since usage-based theories such as cognitive grammar assume an intimate relationship between mental representations of grammar and the processing of instances of language (usage events), corpora have an important role in the development of grammatical analyses. One consequence of relying on corpus data is that individual differences in usage tend to be obscured. To overcome this problem and investigate individual differences in spoken usage, we examine a large corpus consisting of the spoken output of six Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 16 publications
(30 reference statements)
2
34
0
2
Order By: Relevance
“…Something that these authorship studies have in common is that the readers are not shown any of the specific word strings that were useful in the attributions. This contrasts with Coulthard (2004), Mollin (2009) and Barlow (2013) where the idiolectal nature of a precise set of collocations is tested. Also, there is often little or no explanation offered as to why word sequences were or were not useful in these studies.…”
Section: Empirical Evidence For Idiolectal Word Stringsmentioning
confidence: 99%
See 4 more Smart Citations
“…Something that these authorship studies have in common is that the readers are not shown any of the specific word strings that were useful in the attributions. This contrasts with Coulthard (2004), Mollin (2009) and Barlow (2013) where the idiolectal nature of a precise set of collocations is tested. Also, there is often little or no explanation offered as to why word sequences were or were not useful in these studies.…”
Section: Empirical Evidence For Idiolectal Word Stringsmentioning
confidence: 99%
“…Despite the methodological differences across these studies, Coulthard (2004) Mollin (2009) and Barlow (2013) all provide corpus-derived evidence that supports of the notion of idiolectal word strings. In an authorship context, however, where word strings have been used to attribute texts to their correct authors, they have returned mixed results.…”
Section: Empirical Evidence For Idiolectal Word Stringsmentioning
confidence: 99%
See 3 more Smart Citations